(untitled) (Revista Contexto & Saúde, 2023)
Objective: To map existing literature on mental distress in transgender people. Method: A scoping review was carried out based on the steps of Joanna Briggs Institute (JBI) and following the Preferred Reporting Items of Systematic Reviews and Meta-Analyses Extension for Scoping Review (Prisma-ScR) recommendation. Inclusion criteria were: texts available in full published between 2012 and 2022, in article format, with languages in English, Spanish or Portuguese. The electronic databases used were BVS, Web of Science and CINAHL via Capes portal, Scielo and Scopus using the descriptors “angústia psicológica”; “pessoas transgênero”; “psychological distress” and “transgender persons”, from August to October 2022. Data were analyzed using descriptive statistics, and the synthesis of this analysis was organized by thematic similarity. Results: 24 studies were included in this review. To group relevant information, three main categories were highlighted: "Incidence of mental suffering" which shows the rates of this suffering; "Discrimination and stigmas" which presents the complexity and negative consequences of discrimination and "Impacts of access to health services" that portrays the adversity, in which transgender individuals are unable to enjoy their rights within the different levels of health care. Conclusions: There is evidence of high rates of mental suffering in transgender people, when compared to cisgender people, related to discrimination, prejudice, stigma, lack of social and family support and access to health services.